Challenges for Women Entrepreneurs in Digital Financial Literacy: A Scoping Review (Jurnal Cendekia Keuangan, 2026)
Introduction/Main Objectives: In the digital era, digital financial literacy (DFL) has become a vital competency for women entrepreneurs, especially in developing countries. Novelty: This study contributes to the body of knowledge through a literature review on digital financial literacy among women entrepreneurs. Research Methods: This scoping review explores the challenges they face in acquiring and applying DFL, which includes understanding and using financial technologies such as e-wallets, mobile banking, and digital bookkeeping. Despite its potential to enhance business efficiency, transparency, and access to financing, women entrepreneurs often encounter barriers such as limited access to technology, low digital education, and restrictive social norms. Using the PRISMA-ScR framework, this study analyzes 14 selected articles from the Scopus database published between 2020 and 2025. Finding/Results: The findings reveal four key focus areas: the level of understanding and use of financial technology, the relationship between DFL and business success, barriers to accessing digital financial services, and the role of training and education in improving DFL. Research limitation/implications: The practical implication of this study is the need to develop a digital financial literacy program tailored to the needs of women business actors. Governments, financial institutions, and civil society organizations can design app-based training, online modules, and community mentoring to improve women's digital skills.